Silver Nanoparticles Synthesized from Citrus aurantium L. & Citrus sinensis L. leaves and Evaluation the Antimicrobial Activity - Zina K. Albahadly (Journal of Global Pharma Technology, 2016)
The increases in incidence of drug resistance among pathogenic fungi have made the search for new anti-microorganism inevitable. Nowadays, the synthesis of metal nanoparticles by using green methods is increased rapidly. We synthesized Silver nanoparticles from Citrus aurantium L. and Citrus sinensis L. leaves. AgNPs biosynthesized were characterized by particle analyzer, zeta potential, Fourier transform-infrared spectroscopy (FTIR), X-ray diffraction (XRD), and UV-Vis spectroscopy to study the diameter of particles, structure properties of samples, and optical spectroscopy properties respectively. The results obtained revealed that size of AgNPs were 60.5 and 31.72 nm for Citrus aurantium L. and Citrus sinensis L. leaves respectively, with crystallized face-centered cubic structure. The AgNPs biosynthesis showed effective inhibitory antifungal activity against Candida albicanns.Keywords: Biophysics, Antibacterial test, Physical properties.